(untitled) (Journal of Geography and Environmental Management, 2016)
The Central Asian region has a great potential of human resources but individual countries sharply differ from each other by indicators such as the size of territory, population, human development, poverty etc. The article considers the Central Asia countries situation in the international ranking of countries by Human Development Index. Indicators showing the level of human development its constituent components and the managing role of the Central Asian countries to these components presented. Indicators of poverty and inequality in the Central Asian region and their role in shaping the quality of life indicators analyzed. During writing an article following methods were used: statistical, cartographic, regional and other methods. Based on the analysis of human development in Central Asian Republic of Kazakhstan is a leader in human development in the region, but environmental problems limit the possibilities for further development of the country. Despite the positive dynamics of human development index growth in Central Asian region, countries continue to be dependent on fossil fuels, inefficient use of energy resources, there is a high level of air pollution. Human development progress that occurred over the past decade in the studied countries can not be continued without major decisive steps to reduce environmental risks.